Damage identification on arched masonry structures using ambient and random impact vibrations - Ramos, Luís F. (2010)
Preservation of architectural heritage is considered a fundamental issue in the cultural life of modern societies. In addition to their historical interest, monuments significantly contribute to the economy of cities and countries by providing key attractions. In this context, structural damage identification at an early stage plays an important role in heritage preservation. Dynamic based methods to assess the damage are attractive tools for this type of structure because they are non-destructive and are able to capture the global structural behavior. The present paper aims at exploring damage in masonry structures at an early stage by vibration measurements. For this purpose, an approach is presented based of dynamic damage identification methods. To evaluate the approach a one arch model was constructed in the laboratory. Afterwards, progressive damage was induced in the arch and sequential modal identification analysis was performed at each damage stage, aiming at finding adequate correspondence between dynamic behavior and internal crack growth. Comparisons between different techniques were made to evaluate which method is more adequate to identify damage in masonry constructions. The dynamic based methods allowed detecting and locating the damage in the specimens.